FeNx/FeSx-anchored carbon sheet-carbon nanotube composite electrocatalysts for oxygen reduction - Bhange, Siddheshwar N.; Soni, Roby; Singla, Gourav; Ajithkumar, T. G.; Kurungot, Sreekumar (ACS Applied Nano Materials, 2020)
Even though various Pt-free electrocatalysts for oxygen reduction reaction (ORR) have been introduced, many of them are found to be active only in alkaline conditions. Considering Nafion, phosphoric acid-doped polybenzimidazole (PBI), and so on as the prominent ionomer membranes, used in the commercially available polymer electrolyte membrane fuel cells (PEMFCs), it becomes important that any development on the Pt-free catalysts should ensure the better ORR performance under acidic conditions. The present work effectively tackles this issue, where an ORR-based catalyst could be prepared with simultaneous incorporation of both Fe-N and Fe-S active sites on in situ generated carbon sheets which are spatially separated by the carbon nanotube (CNT) network. This catalyst shows ability to perform under both acidic and basic conditions. This has been achieved by growing a polyethylenedioxythiophene polymer network in the presence of CNT and melamine followed by its pyrolysis under an inert atmosphere. The catalyst formed at 900 degrees C (PMCNT-900) displays 0.94 V onset potential for ORR under acidic electrolyte conditions, which corresponds to 60 mV overpotential compared to its 40 wt % Pt/C counterpart. Interestingly, in single cell demonstration of Nafion-based PEMFC with PMCNT-900 as the cathode catalyst, the system delivered a maximum power density (PD) of 500 and 275 mW/cm(2) at 60 degrees C under H-2-O-2 and H-2-air feed conditions, respectively. On the other hand, in a single cell test in the anion exchange membrane fuel cell (AEMFC) mode, a maximum power density of 65 mW/cm(2) at 50 degrees C could be achieved with the same cathode catalyst, which is a comparable value obtained while employing Pt/C as the cathode. These results, thus, infer to the efficiency of the catalyst to facilitate ORR under the extreme pH conditions, and particularly its performance under acidic condition reveals its prospect as a potential Pt-free electrocatalyst to serve in the Nafion-based systems.
Keywords: carbon nanotube; electrocatalyst; fuel cell; oxygen reduction reaction; Pt-free ORR

Facile synthesis of CNT interconnected PVP-ZIF-8 derived hierarchically porous Zn/N co-doped carbon frameworks for oxygen reduction dagger - Singla, Gourav; Bhange, Siddheshwar N.; Mahajan, Mani; Kurungot, Sreekumar (Nanoscale, 2021)
In this work, a strategy has been adopted to construct an architecture through the coordination of polyvinylpyrrolidone (PVP) and a monodisperse zeolitic imidazolate framework (ZIF-8), which was entwined by carbon nanotubes (CNTs) firstly, followed by a pyrolysis process to obtain the hybrid catalyst. The meticulous design of the hybrid material using CNTs to interconnect the PVP assisted ZIF-8 derived porous carbon frameworks together produces a hierarchical pore structure and dual-heteroatom (Zn/N) doping (Zn-N/PC@CNT). Without further acid treatment, the hybrid material prepared after pyrolysis at 900 degrees C (PVP-ZIF-8@CNT-900) has been demonstrated as an efficient non-precious metal catalyst for the oxygen reduction reaction (ORR) with its superior stability compared to the commercial 20 wt% Pt/C catalyst in alkaline media. The catalyst shows better performance towards the ORR, with its more positive onset and half-wave potentials (E-onset = 0.960 V vs. RHE and E-1/2 = 0.795 V vs. RHE) than the counterpart system which is free of both CNT and PVP. The high performance of the hybrid catalyst can be ascribed to the co-existence of dual-active sites with hierarchical pore structures originating from the synergistic effects between Zn/N co-doped porous carbon and CNTs. We further demonstrated the single-cell performance by using the homemade system as the cathode catalyst for the Alkaline Exchange Membrane Fuel Cell (AEMFC) system, which showed a maximum power density of 45 mW cm(-2) compared to 60 mW cm(-2) obtained from the 40 wt% Pt/C catalyst.

Fabrication of a 3D iron-modified NiCo2S4 structure on nickel foam as a bifunctional electrocatalyst for overall water splitting - Singla, Gourav; Mahajan, Mani; Bhange, Siddheshwar N.; Kashyap, Varchaswal (New Journal of Chemistry, 2025)
The development of highly efficient bifunctional electrocatalysts that operate effectively in strong electrolytes, with low overpotentials at defined current densities and excellent durability, has become a central focus in research on overall water splitting. In this study, a three-dimensional (3D) sheet-wrapped wire electrocatalyst, composed of Fe-doped NiCo2S4 on nickel foam (NF), was fabricated. This material demonstrated excellent durability for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in an alkaline medium. The uniform distribution of Ni, Co, Fe, and S elements significantly enhanced the electro-catalytic performance. The incorporation of Fe improved activity, with the Fe2.5%-NiCo2S4/NF electrocatalyst achieving overpotentials of 310 mV and 260 mV for the HER and OER, respectively, at a current density of 100 mA cm-2. These results were superior to those of both bare nickel foam and NiCo2S4/NF. The 3D configuration facilitated efficient ion transport and contributed to the remarkable catalytic performance. As a water-splitting electrolyzer in an alkaline electrolyte of 1.0 M KOH, the system delivered a current density of 20 mA cm-2 at a cell voltage of 1.66 V, highlighting the effectiveness of this design strategy.